STUDI PENDISTRIBUSIAN BERAS SEJAHTERA (RASTRA) DI DESA LOKA KECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR MENURUT PERSPEKTIF ISLAM - Novita Novita; Azis Muthalib; Nuddin Nuddin (JEP (Jurnal Ekonomi Pembangunan), 2019)
This study aims to determine the implementation of the distribution system for prosperous rice (RASTRA) in Loka Village, Tirawuta Subdistrict, East Kolaka Regency and the view of Islamic law on the distribution of prosperous rice (RASTRA) in Loka Village, Tirawuta Subdistrict, East Kolaka Regency. This research method is descriptive qualitative. The object of this research is the distribution of prosperous rice systems (RASTRA) distributed to people in need, both those who are classified as poor or incapable and those who fall under the terms of RASTRA recipients. The distribution of subsidized rice (RASTRA) in Loka Village is not in accordance with the concept of distribution in the Islamic Economy Perspective because there is an injustice in the distribution of RASTRA to the underprivileged (poor) people. That the practice of distribution for the average RASTRA in Loka Village is prohibited and is not legal according to Islamic law. The reason can be seen from several aspects, one of which is: from the aspect of injustice and distribution aspects, the even distribution of literature is not appropriate because with such a division it would make the poor less able to meet their needs for rice and this would certainly harm them.